Acoustic Absorption of Mortar Composites with Waste Material - Marco Aurelio STUMPF; Fernanda FLACH; Josiane RESCHKE PIRES; Marlova PIVA KULAKOWSKI (Archives of Acoustics)
This paper presents an investigation about acoustic absorption of mortars with partial replacement of sand by waste (plywood formwork, rice husk, and thermoplastic shoe counters), examining different levels of replacement (0%, 5%, 10%, 25%, and 50%). The measurement of acoustic absorption was performed using a plane wave impedance tube with 100 mm diameter, using mortar samples of 20 mm, in frequency range 200–2000 Hz. Results demonstrated that some composite with waste presented noise reduction coefficient (NRC) above the reference mortar (NRC = 0.0343), such as a composite with 50% rice husk (NRC = 0.2757) and other with 50% of plywood waste (NRC = 0.2052). Since there is virtually no cost or difficulty to use these residuals, it may be concluded that it is a sustainable alternative to improve the acoustic comfort and reduce the impact of the waste on the environment.